Adjuvant‐induced arthritis affects testes and ventral prostate of Wistar rats. (29th August 2019) - Santos, C. R.; Benjamin, A. C. A.; Chies, A. B.; Domeniconi, R. F.; Zochio, G. P.; Spadella, M. A.
Abstract: Background: Rheumatoid arthritis (RA) may reduce the testosterone production, thereby leading to testicular dysfunction and subfertility. Objectives: This study aimed to evaluate whether adjuvant‐induced arthritis (AIA) induces histopathological and morphometric‐stereological alterations on testes with repercussions on the prostate, and alternatively, verifying AIA‐induced direct effects on the prostate, regardless of the testicular involvement. Material and methods: Adult male Wistar rats were sham‐orchiectomized or orchiectomized. Twenty days after the surgery, these animals were injected with vehicle (SHAM and ORQ groups, respectively) or adjuvant ( Mycobacterium tuberculosis ) to induce arthritis (AIA and ORQ/AIA groups, respectively). Forty days later, testes and ventral prostate were processed for histopathological and morphometric‐stereological analyses, as well as to PCNA immunohistochemistry. Collagen deposit was evaluated in prostate. Circulating testosterone levels were determined 15 days post‐AIA induction in SHAM and AIA rats and 40th day in all groups. Results: In the testes, AIA promoted histopathological changes characterized by an increase in the percentage of abnormal tubules and reduction in the height of the seminiferous epithelium, daily production of spermatozoa, and cellular proliferation. In the prostate, AIA decreased the luminal volume of the secretory ducts. In condition of androgenic deprivation due to the orchiectomy, AIA induced proliferation of the prostatic epithelium. Discussion: The effects of arthritis on testes and prostate were observed 40 days post‐AIA induction, possibly results of the hypoandrogenism were already established on 15th day post‐induction, which is related to the decline of the steroidogenesis in the Leydig cells. On the other hand, the joint inflammatory process may also have direct repercussions upon the prostate, regardless of this hypoandrogenism. Conclusion: AIA effects on reproductive tissues may be related to both hypoandrogenism and other direct inflammatory mechanisms. Possibly, these AIA effects on the testes and prostate occur at a stage in which the inflammatory process is most active, about 15–20 days after induction, remaining evident until the 40th day.